2011
DOI: 10.2215/cjn.05530610
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cognitive Function with Albuminuria and eGFR in the General Population

Abstract: SummaryBackground and objectives Recent studies found different associations of cognitive function with albuminuria or estimated GFR (eGFR). Most studies were limited to the elderly or did not take both renal variables into account. Therefore, this study analyzed the association of cognitive function with albuminuria and eGFR in community-dwelling persons aged 35 to 82 years. ResultsThe prevalence of albuminuria Ͻ10, 10 to 29, and Ն30 mg/24 h was 54%, 31%, and 15%, respectively. Mean eGFR (Ϯ SD) was 79 Ϯ 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 38 publications
8
53
5
Order By: Relevance
“…Our findings support previous reports that showed no association between eGFR and cognitive impairment [6,[20][21][22], but contrast to those that did report a significant association [5,9,[23][24][25][26][27][28][29][30]. In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings support previous reports that showed no association between eGFR and cognitive impairment [6,[20][21][22], but contrast to those that did report a significant association [5,9,[23][24][25][26][27][28][29][30]. In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31]. A recent meta-analysis of five population based prospective studies included 27,805 participants, demonstrated a non-significant increased risk of cognitive impairment or dementia in those with an eGFR < 60 ml/min/1.73m 2 , with a significant association found only in those with albuminuria [7].…”
Section: Discussionmentioning
confidence: 98%
“…Second, the PREVEND cohort is enriched for elevated albuminuria, which could induce selection bias, because albuminuria is a risk factor for CVD. 15 However, a sensitivity analysis in a subsample, representative for the general population, did not change results. Finally, the cross-sectional design of this study does not formally allow a firm conclusion on a causal relationship.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…15 Of those with a complete RFFT score, subjects with a history of CVD or stroke (n=311; 5%) or with missing data on components of the FRS or educational level (n=66; 1%) were excluded. Three participants aged <35 years were excluded because their number was too small to form a separate age group.…”
Section: Study Populationmentioning
confidence: 99%
“…The study by Joosten et al (5) in this issue of CJASN addresses this question. Using data from the Prevention of Renal and Vascular End-stage Disease (PRE-VEND) study, a community-based cohort study in the Netherlands, Joosten et al evaluated the association between baseline and longitudinal measurements of albuminuria and eGFR with cognitive function in 4095 participants with a mean age of 55 years.…”
mentioning
confidence: 98%